Họ nguyên hàm của hàm số \(f\left( x \right) = 2x\left( {\sin x + 1} \right)\) là

Quốc Tuấn

New member
Họ nguyên hàm của hàm số \(f\left( x \right) = 2x\left( {\sin x + 1} \right)\) là
A. \({x^2} - 2x\cos x + 2\sin x + C\).
B. \({x^2}\left( {x - \cos x} \right) + C\).
C. \({x^2} + 2x\cos x - 2\sin x + C\).
D. \({x^2} - 2x\cos x - 2\sin x + C\).
 
Chọn đáp án là A
Phương pháp giải:
Sử dụng phương pháp nguyên hàm từng phần.
Lời giải chi tiết:
\(\begin{array}{l}\int\limits_{}^{} {f\left( x \right)dx} = \int\limits_{}^{} {2x\left( {\sin x + 1} \right)dx} = 2\int\limits_{}^{} {x\sin xdx} + \int\limits_{}^{} {2xdx} = 2{I_1} + {I_2}\\{I_2} = \int\limits_{}^{} {2xdx} = {x^2} + {C_2}\\{I_1} = \int\limits_{}^{} {x\sin xdx} = - \int\limits_{}^{} {xd\left( {\cos x} \right)} = - \left[ {x\cos x - \int\limits_{}^{} {\cos xdx} + {C_1}} \right]\\\,\,\,\,\,\, = - x\cos x + \sin x + {C_1}\\ \Rightarrow \int\limits_{}^{} {f\left( x \right)dx} = - 2x\cos x + 2\sin x + {x^2} + C\end{array}\)
Chọn A.